HPV Sensing by CNTFET Array Nanobiosensor. - Kumar D. R, Santhosh; P.V. Rao, Dr (International Journal of Engineering and Technology, 2018)
Women life is threatened by the cervical cancer each time worldwide. The cervical cancer high grade pre cancer is due to HPV E6 and E7 agents. Nano materials show a key role in medical analysis and action. CNTs (Carbon Nano Tube) have very unique electrical and mechanical properties which are useful in the bio-application. The conventional based biosensors can be improved by CNT based biosensors with respect to sensitivity, selectivity and simple in operation. In comparison with the silicon transistors, CNTFET (Carbon Nano Tube Field Effect Transistor) nano device takes less power and performs faster. The research paper covers working of CNTFET based nano biosensor to detect cervical cancer antibody. 4 x 4 CNTFET sensor array is designed to detect antibody variations on CNTFET gate. The sensor current varied from 4.286 ÂµA to 15.435 ÂµA for gate voltage varied from 0.2 V to 1.06 V. The improved 64 CNTFET based biosensor performs better in sensing the analyte of different concentrations.Â Â